The universe unraveling American foreign policy in Cold War Laos - Jacobs, Seth 1964- (The United States in the world., 2013)
During the Eisenhower and Kennedy administrations, Laos was positioned to become a major front in the Cold War. Yet American policymakers ultimately chose to resist communism in neighboring South Vietnam instead. Two generations of historians have explained this decision by citing logistical considerations. Laos's landlocked, mountainous terrain, they hold, made the kingdom an unpropitious place to fight, while South Vietnam - possessing a long coastline, navigable rivers, and all-weather roads - better accommodated America's military forces. The Universe Unraveling is a provocative reinterpretation of U.S.-Laos relations in the years leading up to the Vietnam War. Seth Jacobs argues that Laos boasted several advantages over South Vietnam as a battlefield, notably its thousand-mile border with Thailand, whose leader was willing to allow Washington to use his nation as a base from which to attack the communist Pathet Lao. More significant in determining U.S. policy in Southeast Asia than strategic appraisals of the Laotian landscape were cultural perceptions of the Lao people. Jacobs contends that U.S. policy toward Laos under Eisenhower and Kennedy cannot be understood apart from the traits Americans ascribed to their Lao allies. Drawing on diplomatic correspondence and the work of iconic figures like "celebrity saint" Tom Dooley, Jacobs finds that the characteristics American statesmen and the American media attributed to the Lao - laziness, immaturity, and cowardice - differed from the traits assigned the South Vietnamese, making Lao chances of withstanding communism aggression appear dubious. The Universe Unraveling combines diplomatic, cultural, and military history to provide a new perspective on how prejudice can shape policy decisions and even the course of history.